Embryogenic Callus Formation in Local Cocoa (Theobroma Cacao L.) Clones - Ramli, Asfaliza (2006)
A study on the potential of embryogenic callus formation in KKM 1,KKM 15, KKM 17, KKM 22, KKM 27, KKM 28, PBC 123, PBC 159, MHP 78,MHP 79, MHP 296, AMAZ, GS 29, EET 339 and MJS 47 local cocoa clones which had been released by MARDI was carried out. A sigmoid curve for callus growth, viability and total protein content of stem, leaf, matured and immatured cotyledon derived callus were obtained. Based on this curve, the subculture interval was determined and it shows that the appropriate timing or period for subculture was between 20 to 24 days after the incubation. Obviously in this interval, the growth of callus was enormous and the total soluble protein was the highest. However, the viability was slowly decreased due to browning of the callus. Therefore only the white and friable callus was selected for subcultures. Embryogenic callus was successfully induced for PBC 123 and MHP 296 cocoa clones by using immature cotyledon derived callus. Negative results were obtained for all clones and explants tested using MS as the embryogenic induction medium but positive results were obtained for PBC 123 and MHP 296 clones using DKW and WPM basic media. The combinations of 2 mg/L 2,4-D and 0.25 mg/L Kin was the most successful auxin and cytokinin combination for embryogenic callus induction.. The nodular embryogenic callus of PBC 123 and MHP 296 emerged after the second subculture. Browning of callus occurred during incubation especially at the end of the culture period and was obvious for both clones. Enhancement of the embryogenic induction media by adding nitrogen rich compounds and amino acid such as casein hydrolysate, malt extract and proline did not improve the initiation of embryogenic callus. Instead, more friable callus were obtained from these enhanced media. In direct somatic embryogenesis, 15 cocoa clones had been tested and four clones showed positive results. These clones (MJS 47, GS 29, PBC 123 and PBC 159) were able to produce embryogenic callus from staminodes explants using the protocol previously developed by Li et al (1998). The nodular embryogenic callus of MJS 47, PBC 123, PBC 159 and GS 29 emerged at the cut ends and were transferred onto a secondary callus growth medium and continued to proliferate on this medium. Maturation of the embryogenic callus was carried out in a medium described by Li et al. (1998). The globular callus were pale brown in colour at the early maturation period but turned dark brown after 3 weeks of incubation period. None of the globular callus turned to heart shaped somatic embryo which is the second stage of somatic embryogenesis. The maturation of the globular callus was not achieved and the embryogenic callus became brown and turned non viable at the end of the incubation period. All embryogenic clones showed similar response to the maturation medium. Total soluble polyphenol content of embryogenic callus of PBC 123 after 16 days of incubation was 259.94 ± 15.53 μg/g fresh weight which was relatively lower than the non embryogenic callus (451.19 ± 5.42 μg/g fresh weight). The increment or accumulation of the TSP was almost similar in MHP 296 immatured cotyledon derived callus especially towards the end of the incubation period. Furthermore, the embryogenic callus which were induced from immature cotyledon of MHP 296 and PBC 123 showed high polyphenol accumulation as compared to embryogenic callus induced from staminode of GS 29, PBC 123, PBC 159 and MJS 47. The browning of non embryogenic callus was greater than embryogenic callus. The specific peroxidase activity was slowly increased as the callus became embryogenic. The POD activity was 164.27 ± 9.42 unit/mg protein for GS 29 embryogenic callus while for non embryogenic callus, the activity was around 63.31 ± 9.24 unit/mg protein at 16 days of incubation. Even though a similar pattern of increment could be observed between the embryogenic and non embryogenic callus, the POD activities was higher in embryogenic callus as compared to non embryogenic callus